Requirements For The Establishment Of The Department Of Central Asian Archaeology (Zien Journal of Social Sciences and Humanities, 2024)
This scientific article is devoted to the analysis of the history of the development of archaeology in Central Asia and its modern state. The article also deeply studies the need for the establishment of a department of archaeology in Central Asia and its role in scientific and research activities. It is emphasized that the establishment of a department of archaeology in Central Asia, due to the rich historical and cultural heritage of the region, as well as its place in the global archaeological community, is of not only scientific, but also cultural and educational importance. The article makes proposals for the development of scientific research and educational programs that can be conducted through this new department